Integration of Mathematics Learning with Islamic Values in Elementary Schools - Azzuhro, Manisha; Salminawati, Salminawati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research focuses on integrating Mathematics Learning with Islamic Values at SD IT Daar Al Uluum Range, Asahan Regency. This study aims to discover the program process, implementation, and results of integrating mathematics learning in Daar Al Uluum Kisaran IT Elementary School. The method used in this research is qualitative research with a case study approach. Research data in the form of integration of mathematics learning with Islamic values. Meanwhile, data sources are obtained from students, teachers, and school stakeholders. Data collection techniques through observation, interviews, and documentation. While data analysis, data reduction, data presentation, and conclusions. The results showed that after integration, students who are responsive and easy to understand, then he can talk about Islamic figures briefly. But he only hears stories from his friends for students who are difficult to understand. But also, not infrequently, some students find it difficult to understand; when they listen to their friends tell stories, they can conclude the results from their friends. That way, the integration of learning is expected to produce students who believe in and do charity. The characteristics that appear in students are bravery, honesty, confidence, and responsibility.